High Affinity Ammonium Transporters: Molecular Mechanism of Action - Pantoja, Omar (Frontiers in Plant Science, 2012)
The importance of the family of high affinity ammonium transporters is demonstrated by the presence of these proteins in all domains of life, including bacteria, archea, fungi, plants and humans. The majority of the proteins that have been studied from this family show high affinity and selectivity for ammonium, are impermeable to alkaline cations, saturate rapidly at low mM concentrations and most of them, are also permeable to methylammonium. Crystallization of homologue proteins from bacteria and archea has demonstrated that the functional entity corresponds to a trimer, with each monomer maintaining a conductive pore. Through molecular modelling, it has been demonstrated that even though the identity of the proteins between bacteria/archea with those from plants is below 25%, the latter seem to structure similarly, an observation that has helped to address the functionality of conserved residues by means of mutational analysis. Results have shown that changes in the extracellular binding site of some plant transporters may result in their inhibition or reduction in transport activity, while in E.coli, dissimilar replacements like Phe/Ala or Ser/Leu that eliminate possible π-interactions or H-bonds with ammonium, respectively, lead to more active transporters. Active mutants with changes in the pair of conserved His in the centre of the transporter suggest this residues are dispensable. Additional mutations have identified other important amino acids, both in the entrance of the pore and in cytoplasmic loops. Regulation of this family of transporters can be achieved by interactions of the C-terminal with cytoplasmic loops within the same monomer, or with a neighbour in the trimer. Depending on the interacting residues, these contacts may lead to the activation or inhibition of the protein.